Oblicz :
(1¾) ⁶ × (2/7) ⁶
(0,8) :(2 i 2/3)⁴
(-6,5)³ : (-0,13)³
(4 ½)³ × (-⅔)³×(-2)³
(2 ½) ⁴ × 0,6⁴ × (-1/15)⁴
0,3 ⁴ × ( 2 ⅔) ⁴ : (-4) ⁴
½ ×[(-1)⁸ + (-1)⁸]
(-3 ⅓) ³ × 0,3 ⁴ - (-½)³ × ( 1 ⅓)²
wielkie dzięki ! jesli mozecie wytłumaczcie również jakim sposobem to zrobiliście :D

1

Odpowiedzi

2010-02-28T13:43:02+01:00
A)
(1¾) ⁶ × (2/7) ⁶=
(7/4*2/7)⁶=
(1/2)⁶=
1/64
b)
(0,8) :(2 i 2/3)⁴=
(8/10*3/8)⁴=
81/10000=
0,0081
c)
(-6,5)³ : (-0,13)³
(-65/10*100/13)³=
50³=
125000
d)
(4 ½)³ × (-⅔)³×(-2)³=
[9/2*(-2/3)*(-2)]³=
6³=216
e)
(2 ½) ⁴ × 0,6⁴ × (-1/15)⁴=
-(5/2*6/10*1/15)⁴=
(-3/30)⁴=
81/810000=
1/10000
f)
0,3 ⁴ × ( 2 ⅔) ⁴ : (-4) ⁴=
(-3/10*8/3*1/4)=
0,2⁴=
0,0016
g)
½ ×[(-1)⁸ + (-1)⁸]
1/2*2=
1
H)
(-3 ⅓) ³ × 0,3 ⁴ - (-½)³ × ( 1 ⅓)²=
(-10/3*3/10+1/2)³*( 1 ⅓)²=
(-1,5)³*( 1 ⅓)²=
-3,375*16/9=
-675/20*16/9=
-60
1 5 1